2009
DOI: 10.2134/agronj2008.0135x
|View full text |Cite
|
Sign up to set email alerts
|

Does Skip‐Row Planting Configuration Improve Cotton Net Return?

Abstract: Cotton (Gossypium hirsutum L.) growers want information about alternative planting confi gurations to reduce seed, technology, and other production costs. We evaluated the impact of solid and 2 × 1 skip-row confi gurations on net returns for cotton grown in 25-, 76-, and 102-cm rows based on yield and fi ber quality data from an experiment in adjacent nonirrigated and irrigated fi elds at Milan, TN. Price diff erences for fi ber quality were calculated using USDA-Agricultural Marketing Service spot prices. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…1). Whereas Balkcom et al (2010) found equivalent or higher yields (depending on year) between narrow and standard row spacing, narrow row spacing had higher seeding, planting, and harvesting costs, as compared to standard row spacing, Larson et al (2009) concluded that, although not statistically significant, nonirrigated standard row cotton with solid row configuration had numerically higher NR at 85 ¢ kg -1 cotton lint than narrow row cotton with solid row configuration; however results were dependent on the price of cotton. 13, average NR across all treatments and years was 1711.88 $ ha -1 (SD = 707.09 $ ha -1 ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…1). Whereas Balkcom et al (2010) found equivalent or higher yields (depending on year) between narrow and standard row spacing, narrow row spacing had higher seeding, planting, and harvesting costs, as compared to standard row spacing, Larson et al (2009) concluded that, although not statistically significant, nonirrigated standard row cotton with solid row configuration had numerically higher NR at 85 ¢ kg -1 cotton lint than narrow row cotton with solid row configuration; however results were dependent on the price of cotton. 13, average NR across all treatments and years was 1711.88 $ ha -1 (SD = 707.09 $ ha -1 ).…”
Section: Resultsmentioning
confidence: 90%
“…Standard row spacing with CST had the highest probability of receiving a fiber quality premium (π 1 + π 2 = .7319; Table 11). Although Larson et al (2009) did not consider different tillage treatments, they concluded that standard row spacing had higher uniformity percentages than ultra-narrow row spacing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2008). Some studies have also found no impact of planting density on cotton fiber color (Nichols et al., 2004; Vories et al., 2001), while other studies looking at planting population and color have found a different outcome, with more favorable color at higher densities (Larson et al., 2009; Wrather et al., 2008).…”
Section: Resultsmentioning
confidence: 99%